ON FUSION MATRIX IN N = 1 SUPER LIUVILLE FIELD THEORY - Poghosyan, H.R.; Sarkissian, G.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
We study several aspects of the N = 1 super Liouville theory. We show that certain elements of the fusion matrix in the Neveu–Schwarz sector are related to the structure constants according to the same rules, which we observe in rational conformal field theory.